Winking, blinking, wiggling, and waggling - Moses, Brian (New York : Dorling Kindersley, 2000)
Describes different eyes and ears in the animal kingdom and how they are used.
6 13 27
Keywords: Ear -- Juvenile literature; Ear; Animals; Eye; Eye -- Juvenile literature